Will Situational Leadership and Corporate Culture Still Influence Employee Engagement Within Millenials? - Widhy Firmansyah; Anita Maharani; Ake Wihadanto (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The purpose of this study was to explore the influence of situational leadership and corporate culture on employee engagement. The phenomenon that will be raised is among millennials who work in State-Owned Enterprises. The literature review used to build the research hypothesis is the theories related to situational leadership, corporate culture and employee engagement. The research method referred to to explore this research phenomenon is a quantitative approach, and uses a hypothesis analysis technique with regression (both linear and multiple). The results obtained indicate that all proposed hypotheses are proven. The implication of this research is to show that millennials still have the view that employee engagement is influenced by the role of situational leadership and corporate culture.